Medical Students’ Reactive Anxiety as a Quality Criterion for Distance Learning during the SARS-COV-2 Pandemic - Maria V. Sankova; Olesya V. Kytko; Yuriy L. Vasil'ev; Olga Yu. Aleshkina; Ekaterina Yu. Diachkova; Hadi M. Darawsheh; Aleksandr V. Kolsanov; Sergey S. Dydykin (Emerging Science Journal, 2021)
Background: Numerous studies have shown an effect of rapidly spreading SARS-COV-2 on combined anxiety-depressive disorders and maladjustment syndrome occurrences. Objective: To determine the primary medical students’ reactive anxiety level and the final scores of their educational progress in distance learning during the SARS-COV-2 pandemic. Materials and Methods: The study involved 824 students at medical universities in Saratov and Moscow. The assessment of the reactive anxiety level was carried out according to the State-Trait Anxiety Inventory, STAI; the average score of students' academic performance was calculated according to the data of the technological platform "1C: Enterprise" version 8.4.1. The survey was completed during distance learning in May 2020. The quality of distance learning was compared to a similar score for 2019, when students were trained in a traditional way. Statistical analysis was conducted using Statistica 6.0. Results: It was shown the presence of moderately severe disorders among the primary medical students according to the average score of reactive anxiety (43.28 ± 12.85), that expressed more in females s (p<0.05), After distance learning, lasting 25% of the whole course, the overall performance score in theoretical knowledge did not change significantly (p>0.05) but the practical skills suffered much especially in time trend (p<0.05). Novelty: It was found that a high level of the reactive anxiety negatively affects the students' adaptive capabilities and the education quality. The specificity of programs at different faculties can determine the state of the students' psychological status. Findings:Timely transition to online classes during pandemics helps to preserve the students' mental well-being and the quality of the educational process. The duration of distance learning for a practical course should not exceed 25% of the whole course. Doi: 10.28991/esj-2021-SPER-07 Full Text: PDF